Prevalence of Depression and Anxiety in Chronic Kidney Disease Patients on Hemodialysis - Sidra Farishta, Aimal Khan, Sumayyah Amin, Shahzad Ahmad, Mohammad Sajjad Ali Khan, Waqar Ahmed, Raheela Bano (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Depression and anxiety disorders are common among hemodialysis (HD) dependent chronic kidney disease (CKD) patients. This study determined the prevalence of depression and anxiety in HD-dependent CKD patients. Methods: 146 HD-dependent patients were selected from the dialysis unit, between 20 and 60 years of age. CKD patients not on hemodialysis were excluded from the study. Depression and anxiety were assessed using the hospital anxiety and depression scale (HADS) questionnaire. Patients’ demographic data such as gender, age, and socioeconomic status were recorded. The socioeconomic status was defined as lower class; patients having a monthly income of 5000 to 12000 PKR, middle class; patients having a monthly income of 12000 to 30000 PKR, and upper middle class; patients having a monthly income of > 30000 PKR. Results: A total of 146 CKD patients were enrolled. The mean age was 39.67±12.42 years. There were 82 (56.2%) males and 64 (43.8%) females in our study. The frequency of depression and anxiety in CKD patients in our study was 32.2% and 19.2%, respectively.. The frequency of depression and anxiety in CKD patients in our study was 32.2% and 19.2%, respectively. Depression and anxiety were stratified among age, gender, and socioeconomic status, and the association was statistically significant (P < 0.05). Practical implications: After this research we can easily find the anxiety and depression factor among HD dependent CKD patients. Conclusion: Depression and anxiety are common disorders among HD-dependent CKD patients. Anxiety and depression were observed in 19.2% and 32.2 % of the CKD patients in our study. Keywords: Depression, Anxiety, Hemodialysis, Chronic Kidney Disease, Prevalence, Mortality.